Surveillance of Avian Influenza Viruses in Wild Birds in Areas Adjacent to Epicenter of an out Break in Federal Capital Territory of Pakistan - Khawaja , J.Z.; Naeem, K.; Ahmed, Z.; Ahmad, S. (International Journal of Poultry Science, 2004)
Influenza is a highly contagious acute respiratory disease of avian origin that has caused epidemics and pandemics in humans for centuries. Among these avian influenza viruses (AIV), only serotypes H5 and H7 are considered highly pathogenic in poultry. However, serotype H9N2 has also been found to produce severe respiratory and reproductive tract infections in chickens. The previous studies have suggested that movement of poultry and wild birds play a major role in the spread of influenza viruses to distant areas in a country. The present study was carried out to monitor the prevalence of AIV in wild birds in certain areas of the Pakistan, which were free from infection during the outbreak of November 2003. In this regard, 7 wild bird species were selected and their blood, cloacal swabs and tissue samples were collected both for serological evaluation and virus isolation. The results indicated that antibodies to AIV serotype H9N2 were present in 10% of wild birds, whereas the virus was itself isolated only from 6.72% of the samples. These data provide the evidence regarding the wild birds as one of the major carrier of the AIV infection.